Aspek-aspek Pendidikan dalam Solat - Hj. Ahmad, Abd. Rashid (Jurnal Usuluddin, 1995)
Solat or prayer which is daily ritual of Muslim is by itselt and effective method of education. This article attempts to elaborate the effects of solat education or spirituality, health, morality and social activity with the purpose to indicate that the perfectly performed solat is, in fact, a significant factor in shaping a Muslim’s personality.